Effect of interlocking between porous epoxy microparticles and elastomer on mechanical properties and deformation modes - Du Ngoc, Uy Lan, Dr.; Azhar, Abu Bakar, Dr.; Baharin, Azahari, Dr.; Zulkifli, Mohamad ariff, Assoc. Prof. Dr.; Chujo, Yoshiki (Elsevier Ltd., 2013)
Link to publisher's homepage at http://www.elsevier.com/